Impact of Molecular Weight Variation Among Rubber Clones on the Properties of Vulcanized Latex Films - Karnda Sengloyluan; Nussana Lehman; Rawiporn Promsung; Adisak Keereerak; Jobish Johns; Ladawan Songtipya; Ekwipoo Kalkornsurapranee (Advances in Polymer Technology)
Vulcanized latex films from different Hevea brasiliensis natural rubber clones, including RRIM600, RRIT251, and PB235, were prepared using the creaming process of concentrated latex. The protein content, morphology, molecular weight distribution (MWD), mechanical properties, dynamic mechanical analysis, and thermo-mechanical properties were studied. The morphological characteristics of the Hevea brasiliensis natural rubber clones were analyzed using transmission electron microscopy (TEM). The results indicated that the particle sizes of the three clones ranged from 1.0 to 2.5 µm. Moreover, the MWD exhibited a bimodal pattern in the RRIM600 and RRIT251 clones, leading to a high polydispersity index (PDI) that correlates with protein content. Additionally, the PB235 clone showed higher molecular weight (Mw) than the other clones, which affected the properties of the vulcanized latex films. The mechanical properties, dynamic mechanical properties, thermal properties from temperature scanning stress relaxation (TSSR) analysis, and swelling resistance were also studied. The results indicated that the crosslinked density of the vulcanized latex films is related to the bimodal MWD. This leads to increased physical interactions between the end chains of short and long rubber molecules. Moreover, the crosslinked density is associated with protein content. This study confirms that the MWD and non-rubber components in different natural rubber clones affect the properties of vulcanized rubber.